Photochemical and Antimicrobial Studies of Cinnamaldehyde and its Bioactive Derivatives - A. Khayyat, Suzan; A. Saddiq, Amna (Asian Journal of Chemistry, 2015)
trans-Cinnamaldehyde [3-phenyl-2-propanal] was isolated from essential oil of cinnamon (Cinnamonum verum). Schiff base and chalcone derivatives were synthesized through condensation reaction with acetone, acetophenone and aniline. Chalcone also subjected to photooxidation reaction in the presence of tetraphenylporphin (TTP) as singlet oxygen sensitizer leading to formation of endoperoxide through [2+4] cyclo addition. The endoperoxide undergo further breaking to form six diketone derivative. Antifungal and antibacterial studies were carried out on cinnamaldehyde and its derivatives i.e., chalcone, Schiff base and its dimer. Studies on the antifungal especially Rhizoctonia solani and Penicillium italicum and antibacterial activity against Klebsiella pneumoniae and methicillin resistant Staphylococcus aureus (MRSA) were showed that cinnamaldehyde and its derivatives have good antimicrobial.